The Case of the Disappearing Doll - Parent, Nancy; Disney Storybook Artists (New York, NY Harper, an imprint of HarperCollinsPublishers, 2019)
When her doll Marabelle goes missing, Nancy and her friend Bree become sleuths to crack the case.
Keywords: Fancy Nancy -- (Fictitious character) -- Juvenile fiction; Fancy Nancy -- (Fictitious character) -- Fiction; Lost articles -- Juvenile fiction; Dolls -- Juvenile fiction; Lost and found possessions -- Fiction; Dolls -- Fiction; Early chapter